2008
DOI: 10.1590/s0103-84782008000700031
|View full text |Cite
|
Sign up to set email alerts
|

Rearing system and behavioural adaptation of laying hens to furnished cages

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In contrast, in cage systems, excreta and other wastes drop to the ground, and the probability of chickens acquiring pathogens is lower. This observation is supported by the reports of [ 28 , 29 ], who observed higher morbidity and mortality in chickens reared on deep litter systems than those kept on cage systems.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, in cage systems, excreta and other wastes drop to the ground, and the probability of chickens acquiring pathogens is lower. This observation is supported by the reports of [ 28 , 29 ], who observed higher morbidity and mortality in chickens reared on deep litter systems than those kept on cage systems.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier transfer to laying cages reduces this effect however, and the time of transfer to the laying environment (16 weeks or earlier) has more influence on the numbers of floor eggs than the rearing environment alone. The use of dust baths in furnished cages has been found to be higher in floor-reared, as opposed to cage-reared, hens during the entire laying period (Roll et al., 2008 ). Indeed, cage-reared laying hens may not use dust-bathing substrate at all, as indicated by the accumulation of undisturbed materials in the litter pan in some furnished cages (A.M. Janczak, unpublished data).…”
Section: Rearing Conditions Affecting the Welfare Of Laying Hensmentioning
confidence: 99%
“…Some authors concluded that there seems to be an association between an early start to perch use and later use of perches by laying hens for real nighttime roosting (Heikkilä et al, 2006). Roll et al (2008) showed that floor-reared hens spend more time perching in laying furnished cages than cage-reared hens (7.5 % versus 13.4 %). In this case, rearing condition has an impact on perch use, even if no perch has been provided during rearing.…”
Section: Management Aspects That Affect Perch Usementioning
confidence: 99%